0009 A Comparison of the Effects of Gaboxadol and Sleep Restriction on Sleep Depth Assessed by the Odds-Ratio-Product. (27th April 2018) - Walsh, J K; Schweitzer, P K; Griffin, K S; Younes, M
Abstract: Introduction: Several studies have shown dose-related increases in SWS and low frequency EEG power and reduced wake time and awakenings with gaboxadol (GBX). These changes are similar to those seen with sleep loss, suggesting that GBX may enhance sleep depth. Odds-Ratio-Product (ORP) is a unit-less continuous measure of the relative power in four EEG frequency bands, with values ranging from 0 (deep sleep) to 2.5 (full wakefulness). Excellent correlation was reported between current ORP and probability of arousal in the next 30 seconds (r 2 =0.98), suggesting that ORP is related to sleep depth. We evaluated the effects of sleep restriction (SR) alone or with GBX on sleep depth using ORP. Methods: Forty-one subjects underwent two baseline PSGs followed by four SR nights (5h) with either placebo (21 subjects) or 15 mg GBX (20 subjects). We compared the change from baseline night 2 (first 5h) to SR night 1 and SR night 4 using two measures: ORP during TST and arousal index. Results: During the first SR night, ORP and arousal index did not change with SR alone (-0.01 ± 0.09 and 0.2 ± 3.0/h for ORP and arousal index, respectively; P>.6 for both), but decreased significantly with GBX (-0.11 ± 0.09 and -3.7 ± 5.2/h; P<0.01 for both). These changes were comparable to those observed after four nights of SR alone (-0.07 ± 0.15 and -3.1 ± 3.8/h). The difference in ORP change scores between GBX and SR remained stable across the four SR nights. Importantly, change in ORP was significantly correlated with change in arousal index during the first GBX night (n=20, r=0.50; P<0.02) and when data were pooled across nights and groups (n=82, r=0.46; P<0.001). Conclusion: A single 15 mg dose of GBX reduces ORP and arousal index to the same extent as four nights of SR alone. Augmentation of sleep depth by GBX remains stable across four nights of SR. The correlation between changes in ORP and in arousal index further supports the use of ORP as a continuous measure of sleep depth. Support (If Any):